Biblioteche reali, biblioteche immaginarie Tracce di libri, luoghi e letture - Dolfi, Anna (Moderna/Comparata, 2015)
In his theoretical writings Calvino puts forward a suggestive idea, inspired by Borges, of the library not only as a collection of works, but as a crossed system of combinations. Under this light, literature itself would be a library, continuously subject to changes and aimed at undermining the canonical authors in order to bring out the apocrypha. In fact, if it is true that literature is born from desire and feeds on it, it cannot be satisfied with the data, but strives to project itself in the realm of the hidden, invisible and far away reality. Libraries, then, are not only infinite, but they change the sense of a book according to the section in which it is placed, to its location, to the methods of consultation and use, to the way the book plays with spaces and light, to its coming to the light or its being in search for the shadows (books in skyscrapers or undergrounds). The library is a place where books and readers interact in mythical spaces. Libraries are collections of narratives and not only of the books that survived the catastrophes of history, but also of the burned books, of the books which have been lost or invented. Libraries treasure all books which, by the mere fact of having been at least once written or thought, have left their mark in the world. This charming and precious book, conceived and edited by Anna Dolfi, offers examples from the major modern literature, inviting the readers to reflect on the relationship between paper and celluloid shadows, between inconturnables and marginalia, looking for books inside libraries and libraries inside books. In the background the reader will enjoy the music, the brilliant acting of Carmelo Bene, the strips of the graphics, the architectural projects, the computer screens, and the pages of an unfinished novel by Giuseppe Dessí that speaks of a walled up library and of a cascade of books at the origin of a fiction novel.